Enantioselective Steglich rearrangement catalysed by chiral guanidinium ion pairs - Yang, Ziqi (Nanyang Technological University, 2023)
Ion pairs are universal in chemistry, biology and environmental science. Several experimental tools have been comprehensively used to characterise the structure of ion pairs along with the development of experimental techniques, such as X-ray crystallography, Nuclear Magnetic Resonance spectroscopy, Infrared spectroscopy, etc. Various inorganic, organic and hybrid ion pairs have been well studied by these experimental analyses. Meanwhile, ion pairs have been applied in asymmetric catalysis during the past several decades. In particular, chiral cations have been used as chiral cation phase-transfer catalyst in asymmetric catalysis. Chiral cationic ligands or counteranions have also found application in asymmetric transition-metal catalysis. In this dissertation, novel chiral guanidinium/achiral anionic pyridinyl-sulfonamide ion pairs were designed and synthesised based on two chiral cationic guanidiniums developed by our group named as bisguanidinium (BG) and pentanidium (PN). First, the chiral bisguanidinium and pentanidium ion pairs were produced successfully with simple steps. One of the chiral pentanidium ion pairs was chosen as an example to be characterised comprehensively by various NMR strategies including 1H NMR, 19F NMR, NOE experiments at different temperatures in different solvents (chloroform-d and toluene-d8). Based on the results, the chiral pentanidium ion pair preferred to be compact in nonpolar solvent at low temperatures. The ion-pair structure is also theoretically analysed using density-functional theory study. Subsequently, we applied the novel chiral organic ion pair in asymmetric catalytic Steglich rearrangement of O¬-acylated oxindole derivatives. The results of catalyst screen and condition optimisation indicated that two chiral pentanidium ion pairs containing different pyridinyl-sulfonamide were optimal choices to afford products with various substitutions in good to excellent yields and excellent enantioselectivities. Based on the observation, it is proposed that achiral anionic pyridinyl-sulfonamide is in charge of substrate activation, while the enantioselectivity is achieved by chiral guanidinium/achiral intermediate ion pair. In summary, we reported a concise and effective strategy to design chiral nucleophilic ion-pair catalyst in this dissertation. Simple catalyst synthesis, facile catalyst structure optimisation and promising enantioselective control were all achieved successfully through the novel chiral ion-pair strategy. Meanwhile, NMR techniques are extensively used to comprehend ion pair structural information thoroughly in solution state. This paves the way for the application of the chiral ion-pair with the chiral cation in enantioselective organocatalysis besides asymmetric phase-transfer catalysis.